Implementasi Program Keluarga Harapan (PKH) Sebagai Upaya Meningkatkan Kesejahteraan Hidup Masyarakat Di Kecamatan Abiansemal Kabupaten Badung - Indah Sari, Gusti Agung Ayu Putu Dita; Prabawati, Ni Putu Anik; Yudartha, IlPutu Dharmanu (CITIZEN CHARTER, 2020)
ABSTRACT Program Keluarga Harapan (PKH) is a social protection program which provides cash assistance to Very Poor Households and for family members are required to implement a set of terms and conditions in the fields of education, health and welfare social. Based on the results of research on the implementation of PKH with theory Van Meter Van Horn shows that this program has been able to run well but has not been maximized, because the implementors have been able to understand the program, and there is social support for the implementation of the program so that the program can lead to prosperity, but there are still problems on several indicators such as external communication which has not been maximum, inadequate human resources, and the unavailability of SOPs Keywords : Implementatiion, ProgramKKeluargaLHarapan (PKH), Abiansemal District